Socio-Ecological Conflicts in a Global South Metropolis: Opportunities and Threats of a Potential Greenway in the São Paulo Metropolitan Region - Moreno, Robson da Silva; Braga, Diego Rafael Galvão Cesar; Xavier, Luis Felipe (Frontiers in Sustainable Cities, 2021)
Greenways are a measure of environmental remediation within a broad framework aimed at promoting urban greening and adaptation to climate change. The typical characteristics of large urban agglomerations, including land use (such as commercial, industrial, and residential areas) with few public spaces and fragmented landscapes, make it difficult to apply these solutions to the urban fabric, forcing decision-makers and planners to act in informal settlements, highways, and industrial parks. One proposed area is an enclave with unused or underutilized lots, where fragments of the Atlantic Forest, parks, landfills, and rapidly expanding informal settlements can be found. This manuscript examines the socioeconomic and environmental processes that shaped this potential urban greenway between Santo André, Mauá, and Ribeirão Pires, which are part of the São Paulo Metropolitan Region (SPRM), the largest in South America. A survey was conducted based on municipal and regional plans, the environmental and urban laws of Brazil, and the socioeconomic history of this part of the SPRM. In addition, satellite images were used to analyze land use evolution through geotechnologies. Finally, we prepared land use recommendations, considering opportunities and threats, highlighting the possibilities of protection and expansion of the Atlantic Forest. To this end, we examined the literature on environmental urban planning and design, green infrastructure, and other concepts. This study intends to stimulate researchers, planners, and decision-makers regarding the urban greening process in the Global South. According to the recommendations, this stimulus would develop these concepts according to the real situation of the region, which would combine the protection of wild habitats and urban environmental amenities. However, this effort makes no sense if one of the defining Global South characteristics not addressed is social inequality. Therefore, we recommend that an effort be made to develop and incorporate processes from urban greening in slum upgrading.